Primary balance: Sustainability analysis under uncertainty - Valerie Lankester Campos; Kerry Loaiza Marín; Carlos Monge Badilla (Inter-American Development Bank (IDB), 2020)
This paper analyzes the sustainability of Costa Rican sovereign debt within the intertemporal budget constraint framework, which is complemented with the estimation of the fiscal reaction function and a risk assessment under the fan chart methodology using annual data from 1974 until 2018. Results show that fiscal behavior has been unsustainable for specific episodes in the long run, and in the short run there have been few instances of debt sustainability since the economic crisis of the early 1980s. Given that a major fiscal reform was approved at the end of 2018, an evaluation of its impact on the path of adjustment of primary balance, considering uncertainty, is included.
Keywords: C22; H63; C15; E62; 330; Debt sustainability; Primary balance; Fiscal reaction function; Risk assessment; Fan chart